Participo logo existo: uma análise sobre a propagação de informações e a percepção de existência nas redes sociais - Colombo, Grazziani Barreto (2015)
This research has as object social networks, specifically Facebook, including participations and interactions on the network. The aim is to investigate the phenomenon of the spread of information under the following approach: to participate is to exist. To that end, variables of influence, communication and reputation involved in the spread and in the forms of participation, which qualify the existence of individuals in the network were studied. The issue involved is that user's forms of participation on social networks are in a transitional movement that changes his perception of existence in the digital environment. There is no stability among the types of interactions that generate the spread of information. These forms are linked to the current structures of social networks: if they change, the forms of participation are also changed, and therefore, the feedback from peers and their perception of existence on the network. The spread also depends on the network algorithm, which defines the rules and content distribution thresholds. Thus, for the diffusion to happen, two decision thresholds will be needed: the user's and the algorithm's. The hypothesis is that user participation qualifies its existence on online social networks. To participate is to exist. Through Granovetter's studies - on the forces between the connections of users and decision thresholds in collective participation, Gladwell and Christakis - about the influences of network connections - the project presents theoretical grounds to advance in the understanding of the dissemination of information on social networks. Users' strong ties are crucial cogs to the scope of the two thresholds within the network. The analyzed case is the "Ice Bucket Challenge", a movement in favor of the Amyotrophic Lateral Sclerosis Association (ALSA). It worked as follows: a person would pour a bucket of water with ice on his head and challenge three others to do the same within 24 hours or donate $ 100 to the association. The message reached tens of millions of people and led the Association to raise 45 times more donations than the previous year. The clarification sought about how the spread of information in social networks and its direct relationship with the existence of individuals, makes it possible the raise of new issues and analysis related to algorithms decision thresholds, as well as new definitions of what is to participate of/to belong to a social network